THE MOBILITY OF NATSUME SOSEKI TO LONDON AND HIS CULTURAL ADAPTATION IN 'RONDONTŌ' - Laily Raff Firdausy; Syahrur Marta Dwi Susilo (UIN Raden Mas Said Surakarta, 2022)
The mobility from East to West in nowadays perspective might be very different from that of the old days. This paper discusses the mobility of Natsume Soseki from Japan to London in the early 1900s and the cultural adaptation he does there. This research applied descriptive analysis method and the cultural adaptation theory with a novel entitled Rondontō as the material object. Some studies related to this were use as both references and supporting instruments. The findings showed that the mobility of Soseki to London is indeed affects many things in his life. However, from the cultural adaptation perspective, it appears that Soseki does not adapt well to his new society in the city. Though he accepts his new environment and also communicate well with the host or Londoners, but the acceptance of the host and the pressure to adapt have led him to uncomfortable situation. These factors affect the functional fitness where he is not expecting much from the new environment as well as his psychological health where he feels like not belonging to the place. Despite the uncomfortable situation, the mobility gives him an important experience and affects much to him, especially his works and life as a scholar of English literature.